Characterization of the Beckwith‐Wiedemann spectrum: Diagnosis and management. Issue 4 (30th August 2019) - Duffy, Kelly A.; Cielo, Christopher M.; Cohen, Jennifer L.; Gonzalez‐Gandolfi, Christina X.; Griff, Jessica R.; Hathaway, Evan R.; Kupa, Jonida; Taylor, Jesse A.; Wang, Kathleen H.; Ganguly, Arupa; Deardorff, Matthew A.; Kalish, Jennifer M.
Abstract: Beckwith‐Wiedemann syndrome (BWS) is the most common epigenetic overgrowth and cancer predisposition disorder. Due to both varying molecular defects involving chromosome 11p15 and tissue mosaicism, patients can present with a variety of clinical features, leading to the newly defined Beckwith‐Wiedemann spectrum (BWSp). The BWSp can be further divided into three subsets of patients: those presenting with classic features, those presenting with isolated lateralized overgrowth (ILO) and those not fitting into the previous two categories, termed atypical BWSp. Previous reports of patients with BWS have focused on those with the more recognizable, classic features, and limited information is available on those who fit into the atypical and ILO categories. Here, we present the first cohort of patients recruited across the entire BWSp, describe clinical features and molecular diagnostic characteristics, and provide insight into practical diagnosis and management recommendations that we have gained from this cohort.